2005
DOI: 10.1007/s00335-004-2439-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel polymorphism in the 5′ untranslated region of theporcine cytochrome b5 (CYB5) gene is associated with decreased fat androstenone level

Abstract: Raising intact male pigs would have a significant economic impact on the pork industry; however, the presence of 16-androstene (a major cause of boar taint) in meat from male pigs would be highly objectionable to consumers. In pigs, a positive correlation has been found between cytochrome b5 (CYB5) and production of 16-androstene. The search for polymorphism of CYB5 and functional analysis of polymorphism found should have an important impact on the efforts to develop genetic markers to select for low androste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…It is unclear as to why the polymorphism in gene CYB5A in the present study affects androstenone levels in plasma, but not in fat. In contrast, Lin et al (2005) and Peacock et al (2007) observed the effect of CYB5A genotype on fat androstenone levels. On the other hand, within breed analysis demonstrated that this effect was significant only in some breeds (Peacock et al, 2007).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…It is unclear as to why the polymorphism in gene CYB5A in the present study affects androstenone levels in plasma, but not in fat. In contrast, Lin et al (2005) and Peacock et al (2007) observed the effect of CYB5A genotype on fat androstenone levels. On the other hand, within breed analysis demonstrated that this effect was significant only in some breeds (Peacock et al, 2007).…”
Section: Discussionmentioning
confidence: 72%
“…CYB5 is an important regulator of 17,20-lyase activity of P450C17, the enzyme essential for steroidogenesis (Pandey and Miller, 2005) and particularly for androstenone biosynthesis (Meadus et al, 1993). Genetic polymorphisms in the porcine gene coding for CYB5A result in different phenotypes with respect to the ability to express boar taint due to androstenone (Lin et al, 2005). In the present study, the effect of this polymorphism on the levels of boar taint and sexual development in Swedish pig populations has been investigated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…I) and a SNP at base 8 upstream of the ATG in the CYB5 5'UTR has been identified [24]. This SNP is associated with a significant decrease in CYB5 protein expression (in vitro demonstration) and a low level of androstenone in the fat of animals from a variety of European breeds [24]. The putative location of CYB5 in the porcine genome (Tab.…”
Section: Genes Involved In the Testicular Synthesis Of Androstenonementioning
confidence: 99%
“…However, only a few studies have reported SNPs in these genes that are correlated with levels of boar taint. These include an SNP in the CYP2E1 promoter (Skinner et al, 2005), an SNP in the coding region of CYP2E1 (Skinner et al, 2005;Lin et al, 2006), a single base deletion in the coding region of CYP2A (Lin et al, 2004a), and an SNP in the coding region of SULT1A1, which may all be related to skatole deposition (Lin et al, 2004b), and an SNP in the 5 0 untranslated region of CYB5 related to decreased androstenone synthesis (Lin et al, 2005). The importance of some of these markers was not supported by other studies (Skinner et al, 2006), and this may be due to the small number of animals or differences in the breeds used in these studies.…”
Section: Genetic Effects On Boar Taintmentioning
confidence: 99%